The Effect of Leadership Effectiveness on the Work Effectiveness of the Staffs - Hennij Lennij Suot (Journal of International Conference Proceedings (JICP), 2018)
This research analyzed the effect of leadership effectiveness on employee effectiveness. The object of this research is Universitas Negeri Manado as the Higher Education Institution. Research problem refers to data phenomenon in Universitas Negeri Manado. The fact presents that the staffs do not have maximum presence since they only go to work for 18 days per month (81%). The average of work contribution is only approximately 6 hours a day, but the staffs are required to attend for 8 hours a day. The problem is: how to increase the employee effectiveness. The hypothesis from this research has been formulated that there is a direct positive influence of the leadership effectiveness on the effectiveness of the employees. The sample method is proportional random sampling technique. The research includes 102 respondents who are the employees of Universitas Negeri Manado.The data were analyzed by using simple linier regression. The result indicates that the leadership effectiveness has given the positive direct effect on employees effectiveness. Keywords: Leadership Effectiveness and Work Effectiveness.